Pengaruh Pengungkapan Corporate Social Responsibility pada Nilai Perusahaan Dengan Profitabilitas dan Leverage Sebagai Variabel Moderasi - Rady Darmastika, I Wayan; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
This study aims to obtain empirical evidence of the influence of Disclosure of Corporate Social Responsibility (CSR) on Corporate Value with Profitability and Leverage as a moderating variable. This research was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) in 2013-2016. The number of samples in this study was 41 companies with 164 observations because there were 3 mining companies that did not have complete information needed in the study. The data analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the analysis of this study it was found that the disclosure of corporate social responsibility has a positive effect on the value of the company. Profitability strengthens the influence of corporate social responsibility disclosure on company value while leverage weakens the influence of corporate social responsibility disclosure on company value. Keywords : Company value, corporate social responsibility